EFFICIENCY OF ULTRAVIOLET INTRAVASCULAR LASER IRRADIATION OF BLOOD IN THE TREATMENT OF HORSES WITH INJURIES OF THE MUSCULOSKELETAL SYSTEM - Скриль, В. Ю. (Scientific Progress & Innovations, 2013)
The results of the effectiveness of the use of ultraviolet blood irradiation intervascular laser treatment for treatment of horses with injuries of musculoskeletal system by the dynamics of clinical indicators are presented. It is proved that five time irradiation of blood once a day lasting ten minutes in combination with local rubbing cream for joints “Alezan” compared with only its local application is more efficient method, as tendency for rapid disappearance of lameness and signs of inflammatory reaction are recorded.